2016
DOI: 10.1093/jxb/erw383
|View full text |Cite
|
Sign up to set email alerts
|

Plant growth responses to elevated atmospheric CO2are increased by phosphorus sufficiency but not by arbuscular mycorrhizas

Abstract: HighlightExperiments combining elevated CO2 (eCO2), mycorrhizas and soil P level revealed that eCO2 increases the P use efficiency in Medicago truncatula and Brachypodium distachyon but not their mycorrhiza-mediated P uptake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 80 publications
(132 reference statements)
5
29
0
Order By: Relevance
“…() reported that eCO 2 generally had a positive influence on AMF colonization. However, the effects of eCO 2 and P supply on the AMF varies with the host plant type, AMF species and climate factors, as well as soil biology and chemistry (Jakobsen et al ., ). Here, we report that growth under eCO 2 significantly improved AMF development on tomato roots, especially under P starvation conditions (Figs b, S1c).…”
Section: Discussionmentioning
confidence: 97%
“…() reported that eCO 2 generally had a positive influence on AMF colonization. However, the effects of eCO 2 and P supply on the AMF varies with the host plant type, AMF species and climate factors, as well as soil biology and chemistry (Jakobsen et al ., ). Here, we report that growth under eCO 2 significantly improved AMF development on tomato roots, especially under P starvation conditions (Figs b, S1c).…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, N 2 fixation (Fig. Greater access to C (Tissue et al 1996, Hungate et al 1999Fitter et al 2000, de Graaff et al 2006, Cernusak et al 2011, Jakobsen et al 2016, Terrer et al 2016) and stoichiometric demand for N and P (Barrett et al 1998, Niu et al 2013) likely led to the observed increase in nutrient acquisition strategies under elevated CO 2 . 4), and AM colonization (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The M. truncatula Jemalong A17 ecotype is commonly used as the model for the study of many aspects of the mycorrhizal symbiosis, from whole plant physiology through to questions of fundamental plant biology (Jakobsen et al, ; Javot, Penmetsa, Terzaghi, Cook, & Harrison, ). This ecotype is generally characterized by vigorous colonization by AMF and large positive mycorrhizal growth responses in response to abiotic stresses such as nutrient deficiency/toxicity (Watts‐Williams et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the variation in the noninoculated plants in the present study was much higher than that found by Sutka et al (), suggesting that M. truncatula has the capacity for a wider range of water transport than A. thaliana . However, M. truncatula can be very responsive in terms of physiology (e.g., growth and nutrient uptake) to AMF inoculation (Jakobsen et al, ; Watts‐Williams, Jakobsen, Cavagnaro, & Grønlund, ) and thus may often associate with AMF in its natural environment; therefore, the lower variation in L o observed in the inoculated plants may be more representative of the “natural” state for M. truncatula , and those noninoculated accessions that have very low L o (Libya and A17) may be particularly affected by the lack of AMF inoculation.…”
Section: Discussionmentioning
confidence: 99%